Canine Experimental Autoimmune Encephalomyelitis: : Potential Therapeutic Effect of Fingolimod - Yun, Taesik; Chae, Yeon; Lee, Dohee; Koo, Yoonhoi; Kim, Hakhyun; Chang, Dongwoo; Kang, Byeong-Teck (Acta Scientiae Veterinariae, 2025)
Background: Meningoencephalitis of unknown etiology (MUE) is a representative sterile inflammatory disease of the central nervous system (CNS) in dogs. The treatment involves the use of immunosuppressive therapies. Despite intensive immunosuppressive therapy, the survival time of MUE remains short. Fingolimod is a novel immunomodulatory drug primarily used to treat human neuroinflammatory diseases such as multiple sclerosis. However, fingolimod has not yet been used in veterinary medicine. Therefore, this study aimed to identify the potential therapeutic effect of fingolimod as an alternative treatment agent for MUE in dogs, using a canine experimental autoimmune encephalomyelitis (EAE) model. Materials, Methods & Results: The canine EAE model was induced using brain tissues obtained from client-owned dog. Eight grams of forebrain tissue were homogenized in an ice bath for 5 min with phosphate-buffered saline. The resulting suspension was emulsified with an equal amount of Freund’s complete adjuvant. A laboratory Beagle dog was subcutaneously injected with the homogenate in the axillary and inguinal regions (a total of 4 sites) under sedation. The dog received a booster injection 7 days later using the same procedure as the 1st injection. After 25 days of the 1st injection, the dog showed decreased activity and hyporexia. When a magnetic resonance imaging (MRI) examination was performed to determine whether the inflammatory lesion was induced, a lesion in the left white matter of the frontal lobe was identified as hyperintense in T2-weighted and fluid-attenuated inversion recovery images and hypointense to isointense in T1-weighted images. Additionally, cerebrospinal fluid analyses revealed a slight increase in total protein concentration and severe mononuclear pleocytosis. The EAE dog was prescribed oral fingolimod [0.05 mg/kg once daily]. At 14 and 28 days post-fingolimod therapy, assessments of clinical signs and 2nd and 3rd MRIs were performed to evaluate therapeutic effectiveness. The clinical signs and most lesions were no longer observed. CSF analysis results were also normal at 14 and 28 days after the commencement of fingolimod therapy. Discussion: The canine EAE model and MUE share several key similarities, making the EAE model a valuable tool for studying MUE. Both conditions are characterized by immune-mediated inflammation of the CNS, leading to demyelination and neurological deficits. The treatment approaches for both conditions often involve the use of immunosuppressive therapies to control inflammation and prevent further neurological damage. These similarities in pathogenesis, clinical presentation, and therapeutic strategies emphasize the relevance of the EAE model in understanding the mechanisms underlying MUE and in developing effective treatments for MUE. Fingolimod was known to be well tolerated and effective, causing a swift decrease in peripheral lymphocytes without any adverse effects at oral doses ranging from 0.01 mg/kg to 0.1 mg/kg in dogs. Despite being a single case, this study evaluated fingolimod as a novel immunomodulatory agent for MUE. When applied for 4 weeks in a canine EAE model, fingolimod revealed a remarkable therapeutic effect by showing recovery of clinical signs, resolution of MRI lesions, and normalization of abnormal CSF findings. Therefore, fingolimod has shown potential as an alternative novel treatment agent for dogs with MUE. Keywords: dog, EAE, fingolimod, treatment, meningoencephalitis, MUE, S1PR.